The use of sling vs sphincter in post‐prostatectomy urinary incontinence. (3rd June 2015) - Van Bruwaene, Siska; De Ridder, Dirk; Van der Aa, Frank
<x xml:space="preserve">Abstract</x> The artificial urinary sphincter (AUS) is considered the 'gold standard' in post‐prostatectomy urinary incontinence. However, in recent years, male slings have gained much popularity due to the ease of surgery, good functional results and low complications rates. This review systematically shows the evidence for the different sling systems, describes the working mechanism, and compares their efficacy against that of the AUS. Furthermore subgroups of patients are defined who are not suited to undergo sling surgery.